The impact of greenhouse conventional and organic pepper (Capsicum annuum) over the soil-plant component, in Alfaro Ruiz, Costa Rica - Samaniego Sánchez, Rubén D. (2006)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2006